The Application Of Outdoor Learning Method To Improve Nineth Grade Students' Arabic Speech Skills At Ponpes Darul Ulum Indragiri - Hasim, Muhamad Fuad; Baihaqi, M; Sakinah, Nelly; Humaidah, Ulil Irzaqotul; Ramadhani, Arya Pratama; Al-Hakim, Ahmad Ghulam Zaidirrohman; Masitho, Dewi Nur; Wahid, Abdurrahman (STIQ Amuntai, 2025)
This study investigates the effectiveness of the outdoor learning method in enhancing Arabic speaking skills among 11th-grade students at Pondok Pesantren Darul Ulum Indragiri. Employing a one-group pretest-posttest experimental design, 12 students were assessed using structured tests before and after receiving treatment through four sessions of outdoor learning activities. Data were analyzed quantitatively using SPSS 27.0. Results show a significant improvement in students' speaking skills, with average scores rising from 62.77 (pre-test) to 93.33 (post-test). The paired sample t-test yielded a significance value of 0.000, confirming that the method effectively improves speaking performance. The outdoor setting increased student engagement and provided a contextual environment conducive to practicing Arabic in real-life scenarios. This method not only improved vocabulary recall but also boosted student confidence and participation. Findings support the integration of outdoor learning into Arabic language instruction, particularly in environments that demand higher student interaction. Future research should involve a larger population and longer duration to validate the long-term impact of this method.